2022
DOI: 10.1021/jacs.2c06677
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Radical Carbonylation by Philicity Regulation

Abstract: Carbonylation reactions involving CO as readily available C1 synthons have become one of the most important tools for the construction of carbonyl compounds from feedstock chemicals. Despite numerous catalytic methods for carbonylation reactions proceeding via ionic or radical pathways, an inherent limitation to these methods is the need to control switchable single and double carbonylative formation of value-added products from the same and simple starting materials. Here, we describe a new strategy that expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Instead, radical-trapping adducts 16 and 17 were detected by high-resolution mass spectrometry (HRMS) or isolated in high yield, respectively. These outcomes imply the possible engagement of cyanoalkyl radical 2a-B that should be formed from iminyl 2a-A via β-C–C bond cleavage. , Additionally, when the radical clock substrate 18 was reacted with oxime ester 2a and adamantyl acid 4s , ring-opening product 19 was isolated in good yield with excellent enantioselectivity (92% ee), suggesting the intermediacy of benzylic-type radical 18-B formed from 18-A through ring-opening of the cyclopropyl group (Figure B). Collectively, these results provide strong evidence of a radical process.…”
Section: Substrate Scope Of Carboxylic Acidsmentioning
confidence: 97%
See 1 more Smart Citation
“…Instead, radical-trapping adducts 16 and 17 were detected by high-resolution mass spectrometry (HRMS) or isolated in high yield, respectively. These outcomes imply the possible engagement of cyanoalkyl radical 2a-B that should be formed from iminyl 2a-A via β-C–C bond cleavage. , Additionally, when the radical clock substrate 18 was reacted with oxime ester 2a and adamantyl acid 4s , ring-opening product 19 was isolated in good yield with excellent enantioselectivity (92% ee), suggesting the intermediacy of benzylic-type radical 18-B formed from 18-A through ring-opening of the cyclopropyl group (Figure B). Collectively, these results provide strong evidence of a radical process.…”
Section: Substrate Scope Of Carboxylic Acidsmentioning
confidence: 97%
“…Next, we briefly investigated the generality of this three-component photo-ATRA-type reaction by reacting a range of oxime esters and (hetero)­aryl alkenes with carboxylic acids 3a , 3c , 4m , or 4s (Table ). A series of oxime esters 2b – f , which were readily prepared from the cyclobutanone derivatives, were briefly examined (Table a). It was found that structural variation has no obvious effect on the reaction efficiency and enantioselectivity.…”
Section: Substrate Scope Of Carboxylic Acidsmentioning
confidence: 99%
“…32,33 Visible-light-induced photoredox reactions involving alkyl radicals generated from organoboron species have been shown to be an important tool for the preparation of high-value organic compounds. [32][33][34][35][36][37][38] Since the pioneering work reported by the Molander 37 and Akita 38 groups, trifluoroborates, which are synthesized from boronic esters or boronic acids, have been widely used for various organic transformations, mainly because of their low oxidation potentials [~1.2 V vs saturated calomel electrode (SCE)] and bench stability. In recent years, other boric acid derivatives, such as borate esters, borooctene, and their metal salts (e.g., lithium alkyl borates based on boron ferrocene), have also been explored to enrich their applications (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, mixtures of mono and double carbonylation products were identified; however, the selectivity was challenging to bias. Chen, Xiao, and colleagues built on these observations and developed a switchable radical carbonylation protocol enabled by photoredox catalysis (Figure C) . Ketoamides could be generated through the double carbonylation of nitrogen radical cations with oxime ester derived cyanoalkyl radicals.…”
Section: Palladium-catalyzed Carbonylations In Streamlining Complex N...mentioning
confidence: 99%